Development of the Ultra-Wideband Circular Antenna Array - Ballandovich, S. V.; Antonov, Yu. G.; Kostikov, G. A.; Liubina, L. M.; Sugak, M. I. (2020 Systems of Signal Synchronization, Generating and Processing in Telecommunications (SYNCHROINFO), 2020)
The present paper describes the design of an ultrawideband circular antenna array for direction finding applications. The proposed antenna array consists of nine identical biconical dipoles, has a diameter of 522 mm, its operation frequency band is 0.3-3 GHz. Numerical and experimental results for biconical antenna under study are presented. A special feature of the proposed array element design is the possibility of its production by cheap laser-cutting technique and its modular construction. The key criteria for selecting an element for implementing the direction finding antenna array is the antenna factor. Influence of mutual coupling and shading effect in the antenna array have been also estimated.